1993
DOI: 10.2514/3.56879
|View full text |Cite
|
Sign up to set email alerts
|

Fountain Flows Produced by Multijet Impingement on a Ground Plane

Abstract: A numerical and experimental study is made of the characteristics of three-dimensional fountain flows generated by the impingement of two-or three-axisymmetric turbulent jets on a ground plane through the influence of a low-velocity crossflow. This study provides a basis to understanding more complex flowfields in numerous practical situations including jet-powered vertical/short takeoff and landing (V/STOL) aircraft. The simulations are based on the solution of the time-averaged Navier-Stokes equations and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Early attempts to acquire turbulence data used hot-wire anemometry (14,15) but this technique is limited to low flow speeds Early work revealed that the fountain is quite sensitive to small imbalances between the jets and appears to be unstable under certain conditions (3) . Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (4) . Velocities normal to the axis of the fountain upwash have been found to be in the region of twenty to thirty percent of the jet exit velocity, at least for incompressible experiments (4,5) .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Early attempts to acquire turbulence data used hot-wire anemometry (14,15) but this technique is limited to low flow speeds Early work revealed that the fountain is quite sensitive to small imbalances between the jets and appears to be unstable under certain conditions (3) . Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (4) . Velocities normal to the axis of the fountain upwash have been found to be in the region of twenty to thirty percent of the jet exit velocity, at least for incompressible experiments (4,5) .…”
mentioning
confidence: 96%
“…Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (4) . Velocities normal to the axis of the fountain upwash have been found to be in the region of twenty to thirty percent of the jet exit velocity, at least for incompressible experiments (4,5) . Positioning of the fountain is largely dependent upon the momentum ratio of the opposing wall jets with differences in their relative thicknesses causing the fountain to appear to lean (6) .…”
mentioning
confidence: 96%
“…The fountain is quite sensitive to small imbalances between the jets (4,5) and appears to be unstable under certain conditions (6) . Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (7,8) . Velocities normal to the axis of the fountain upwash have been found to be in the region of 20 to 30% of the jet exit velocity, at least for incompressible experiments (8,9) .…”
Section: Aims and Objectivesmentioning
confidence: 97%
“…Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (Barata, 1993). Velocities normal to the axis of the fountain upwash have been found to be in the region of twenty to thirty percent of the jet exit velocity, at least for incompressible experiments (Barata, 1993;Behrouzi and McGuirk, 1993). Positioning of the fountain is largely dependent upon the momentum ratio of the wall jets with differences in their relative thicknesses causing the fountain to appear to lean (Siclari, Hill and Jenkins, 1981).…”
Section: Introductionmentioning
confidence: 96%
“…Early work revealed that the fountain is sensitive to small imbalances between the jets and appears to be unstable under certain conditions (Skifstad, 1970). Further studies have reported turbulence intensities in the fountain upwash as high as 50% and a much greater rate of spreading in the fountain when compared to a free jet (Barata, 1993). Velocities normal to the axis of the fountain upwash have been found to be in the region of twenty to thirty percent of the jet exit velocity, at least for incompressible experiments (Barata, 1993;Behrouzi and McGuirk, 1993).…”
Section: Introductionmentioning
confidence: 99%